MAKNA SIMBOLIS RITUAL LEGHA KIWAN DALAM RITUS KELAS MASYARAKAT MANGGARAI TIMUR: KAJIAN ETNOLINGUISTIK - Fransiskus Sanjaya (Universitas Warmadewa, 2021)
This study aims to describe the symbolic meaning contained in the legha kiwan ritual in the mese class rites or feasts of the people of East Manggarai, Flores, NTT. This research is a type of qualitative research by applying ethnographic principles. The data in this study are snippets of speeches in the legha kiwan ritual. The data sources of this research are substantive data sources and local data sources. The source of substantive data in this study is oral speech in the legha kiwan ritual which has been transcribed into text. Meanwhile, the source of locational data in this study was the East Manggarai Regency area. The data collection methods used were participatory observation and interviews with the watch-record technique and ethnography. The collected data is then classified and typified so that data types are ready to be subjected to data analysis techniques. The data in the study were analyzed using the extralingual equivalent method with contextual data analysis techniques. There are three stages in analyzing data, namely identification, classification, and interpretation. Based on the results of data analysis, it is known that the legha kiwan ritual contains symbolic meanings of respect, hard work, love, intelligence, and hope. Keywords: ethnolinguistic; legha kiwan; symbolic meaning; East Manggarai